Harmoni Lanskap Spiritual dan Kontestasi Komoditas di Gunung Kawi - Amirul Auzar Ch.; Tony Rudyansjah (Antropologi Indonesia, 2019)
In understanding spiritual landscape, human ideas and practices in dealing with something sacred was considered to be connected with history or memory, cosmology, livelihood, power, and social dynamics. These aspects appeared to create structures and agents entangled around something that was considered sacred. Through a study on the sacred sites of Gunung Kawi, this article wants to show how an awareness of spiritual landscape producing and co-existing with commodification practices. Through the intertwined of those two logics—spiritual landscape and commodification—a lot of things in Gunung Kawi, both human and non-human, were behaving as an agent and an object at the same time. The sacred was then created through the interaction between landscape and human framed by spirituality and commodity.